A Tandem Aldol/Desilylation/CuAAC Sequence of Difluoroenoxysilanes and Silyl-α-ketoalkynes to α-Fluoroketone α-1,2,3 Triazole Tertiary Alcohol - Liu, Zhi-Chao; Wang, Tao; Yang, Shengchao; Zhou, Jian; Yu, Jin-Sheng (Synlett, 2025)
A one-pot tandem aldol/desilylation/CuAAC sequence is developed, allowing the facile synthesis of tertiary alcohols featuring an α-difluoroketone moiety and a 1,2,3-triazole at the α position in moderate to good yields, with an operationally friendly manner. While Bi(OTf)3 was the optimal catalyst for the Mukaiyama-aldol reaction of silyl-α-ketoalkynes and difluoroenoxysilanes, CuCl was found to efficiently mediate the alkyne–azide cycloaddition.
Keywords: Aldol/desilylation/CuAAC reaction; Difluoroenoxysilanes; Silyl-α-ketoalkynes; α-Fluoroketone α-1,2,3 triazole tertiary alcohol